2015
DOI: 10.1016/j.trim.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the mTOR inhibitor everolimus and the PI3K/mTOR inhibitor NVP-BEZ235 in murine acute lung injury models

Abstract: The mammalian target of rapamycin (mTOR) is a key signaling kinase associated with a variety of cellular functions including the regulation of immunological and inflammatory responses. Classic mTOR inhibitors such as rapamycin or everolimus are commonly used in transplant as well as cancer patients to prevent transplant rejection or cancer progression, respectively. Noninfectious drug-induced pneumonitis is a frequent side effect in mTOR-inhibitor-treated patients. Therefore, we tested the effects of the mTOR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The serine/threonine kinase mammalian target of rapamycin (mTOR) is a key signaling kinase linked to several cellular functions including immunological and inflammatory responses. The mTOR inhibition reduced inflammatory cytokines in LPS/oleic acid-induced lung injury model [ 54 ].…”
Section: Oleic Acid-induced Lung Injury and Inflammationmentioning
confidence: 99%
“…The serine/threonine kinase mammalian target of rapamycin (mTOR) is a key signaling kinase linked to several cellular functions including immunological and inflammatory responses. The mTOR inhibition reduced inflammatory cytokines in LPS/oleic acid-induced lung injury model [ 54 ].…”
Section: Oleic Acid-induced Lung Injury and Inflammationmentioning
confidence: 99%
“…Specifically, in the lung, it has been observed that mTOR can regulate the biological activities of pulmonary vascular endothelium and alveolar epithelial cells in lung diseases [ 134 , 135 ]. mTOR forms the catalytic subunit of two complexes, mTORC1 and mTORC2 [ 132 ].…”
Section: Activation Of Mtor Signaling In Lung Function and Chronic Hi...mentioning
confidence: 99%
“…Emodin can reduce the expression of NF-κB, thereby reducing the inflammatory response in ALI [122]. Mammalian target of rapamycin (mTOR) is involved in the regulation of the biological activities of pulmonary vascular endothelial cells and alveolar 5 Oxidative Medicine and Cellular Longevity epithelial cells in ALI and therefore plays an important role in the occurrence and development of ALI [123,124]. The activation of the mTOR signaling pathway may regulate the translocation of HIF-1α from the cytoplasm to the nucleus, thereby increasing the expression of VEGF, increasing the production of inflammatory factors, and exacerbating ALI [123,125].…”
Section: Strategies To Reduce Acute Lung Injury Bymentioning
confidence: 99%